High conductivity and stability intercalated carbonaceous conductors. (October 2022) - Khanbolouki, Pouria; Jayatilaka, Gehan C.; Wang, Chao; Tehrani, Mehran
Highlights: Copper chloride intercalation is scalable and stable up to 500K. It enhances electrical conductivity of different carbonaceous conductors by 10X. Intercalated carbon fibers achieve a 10MS/m electrical conductivity. Intercalation results in a one-step impurity purification and conductivity enhancement. Conduction in CNT yarns is hampered significantly by internal junction resistances. Abstract: Carbonaceous conductors have attracted great interest due to their low density and superior mechanical and chemical properties. Metal halide intercalation is an effective approach for enhancing the electrical conductivity of these conductors. This paper investigates the microstructure, composition, electrical, and mechanical properties of different carbonaceous conductors (pitch carbon fiber, three types of carbon nanotube yarns, and graphene fiber) intercalated with copper chloride. Temperature-dependent conductivity measurements along with Raman spectroscopy, X-ray diffraction, and energy-dispersive X-ray spectroscopy reveal the degree of intercalation in different samples. Intercalated specimens exhibit electrical conductivities at least seven-fold higher than their pristine counterparts, including a 10 MS/m conductivity for intercalated carbon fibers. Interestingly, the intercalation process results in a one-step impurity purification and conductivity enhancement in CNT yarns. Electrical conductivity measurements over cryogenic and elevated temperature ranges (30-500 K) explain conduction mechanisms and demonstrate intercalant stability. This study informs future applications of lightweight conductors by presenting a library of different carbon-based conductors and their structural and property variations. Graphical abstract: Image, graphical abstract